Association of arsenic, lead, and mercury with liver function markers in German outpatients - Zuo, Jiao; Huesker, Katrin; Chen, Xin; Liu, Yvonne; Hocher, Johann-Georg; Reichetzeder, Christoph; Elitok, Saban; Krämer, Bernhard; von Baehr, Volker; Hocher, Berthold (Food and chemical toxicology, 2026)
Chronic exposure to arsenic, lead, and mercury can impair liver function, but their combined impact on hepatocellular (AST, ALT) and cholestatic (ALP) liver enzymes remains poorly defined. We analyzed data from 58,864 German outpatients without known toxic exposure to evaluate independent and synergistic effects of these metals on liver enzymes. Blood levels of arsenic, lead, and mercury were measured, and associations with AST, ALT, and ALP were assessed using multivariable models adjusted for age and sex, including interaction terms. Mercury showed the strongest positive correlation with ALT (p < 0.001), indicating a pronounced hepatocellular effect. Arsenic was associated with increased AST and ALT and decreased ALP (p < 0.001 for all), suggesting both hepatocellular and cholestatic involvement. Lead demonstrated weaker but significant positive associations with all enzymes (p < 0.001). Co-exposure analyses revealed that arsenic plus mercury modestly but significantly increased ALT, arsenic plus lead elevated AST, and high combined arsenic and mercury exposure reduced ALP. Our findings provide new evidence that background exposure to toxic metals, even below occupational thresholds, may subtly impair liver function. Mercury emerged as the most potent hepatotoxin. These results highlight the need to reconsider current environmental safety standards, especially regarding combined exposures.
Online verfügbar: 7. November 2025, Artikelversion: 9. November 2025
Gesehen am 26.01.2026